Effects of Leg Muscle Power Exercise and Leg Length on Power Leg Muscle and 50-meter Breaststroke Swimming Speed - Jukhairsyah, Adri; Soegiyanto, Soegiyanto; Pramono, Harry (Journal of Physical Education and Sports, 2019)
The purpose of this study was to analyze the effect of the leg muscle power training method and leg length on the increase in leg muscle power and the 50-meter breaststroke swimming speed. This research is a quasi-experimental study with a 2x2 factorial design of 20 research samples with a sampling technique using purposive sampling technique. Data analysis techniques using Multivariate Analysis of Variance (MANOVA). The results of this study are there are differences in the effect of front barrier hop training methods and jump to box on the increase in leg muscle power, there is a difference in the effect of the front barrier hop training method and jump to box on the 50-meter breaststroke swimming speed, there is a difference in influence between athletes having long limbs and short limbs on increasing leg muscle power, there is a difference in the effect between an athlete having long limbs and short limbs on the 50-meter breaststroke swimming speed, there is an interaction between leg muscle power training and leg length to increase leg muscle power, there was no interaction between leg muscle power training and leg length to the 50-meter breaststroke swimming speed.